The impact of using community home-based elderly care services on older adults’ self-reported health: fresh evidence from China - He, Yang; Wei, Baojian; Li, Yushang (Frontiers in Public Health, 2023)
Background The rapid population aging in China, characterized by a higher prevalence of illnesses, earlier onset of diseases, and longer durations of living with ailments, substantially engenders challenges within the domain of older adults’ healthcare. Community home-based elderly care services (CHECS) are a feasible solution to solve the problem of older adults’ care and protect older adults’ health. The aim of this study is to investigate the relationship, heterogeneity effects and influential mechanisms between older adults’ use of CHECS and their self- reported health. Methods The study employs the Instrumental Variable technique and empirically investigates the relationship, heterogeneity effects and influential mechanisms between older adults using CHECS and their self-reported health using data from the China Longitudinal Aging Social Survey from 2018. Results The findings indicate, firstly, that using CHECS considerably improves older adults’ self-reported health. Secondly, the heterogeneity test reveals that the effect is more pronounced for older adults who are under the age of 80, have functional disabilities, are free of chronic diseases, have never attended school, reside in lower-income households, are single, rarely interact with their children, and live in central urban or city/county regions. Thirdly, the mechanism test reveals that the “social network effect” and “family care effect” are the key influence channels of using CHECS. Conclusion An empirical foundation for the policy reform of community home-based care for seniors is provided by this study with the limitations to discuss the other socioeconomic aspects such as government health expenditure and discuss the specific services aspects such as health care. The findings carry substantial implications for improving the health of older individuals and provide suggestions for establishing a socialized aged care system in China.